The impact of network sharing on competition: The challenges posed by early versus mature 5G - Zoltán Pápai; Aliz McLean; Péter Nagy; Gabor Szabo; Gergely Csorba (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
The rollout of fifth generation mobile networks is progressing around the world, but 5G looks especially expensive compared to previous generations. Network sharing between two or more mobile operators is an obvious way to attain significant cost savings, but may also raise competition concerns. This paper first distinguishes between early and mature 5G, and then discusses the expected changes mature 5G brings to the assessment of active mobile network sharing agreements from a competition policy point of view. We focus on the three main concerns where 5G may bring the most significant changes in the evaluation compared to 4G: service differentiation, cost commonality between the parties and the parties' ability and incentives to grant access to critical inputs to downstream competitors. For each of these concerns, we show that they are not easy to substantiate and in some cases the concerns may even become less grave than under 4G.
Keywords: K21; L13; L41; 330; mobile telecommunication markets; network sharing; competition policy; competitive assessment; 5G